Play Framework cookbook : over 60 hands-on recipes to create dynamic and reactive web-based applications with Play 2 /: over 60 hands-on recipes to create dynamic and reactive web-based applications with Play 2. (2015) - Reelsen, Alexander; Inductivo, Giancarlo
No abstract available